Decoupled Feed Forward Voltage Oriented Controller For DFIG Under Balanced And Unbalanced Fault Conditions - Dileep Kumar Varma; Y. P. Obulesh; Ch. Sai Babu (Institute of Advanced Engineering and Science, 2015)
As wind power penetration increases continuously in total Power Generation, the wind turbines are necessary to stay connected to grid even under grid disturbances. An enhanced control strategy for DFIG is proposed in the present paper to meet the latest grid codes set by grid operators. The decoupled current controller implemented in grid voltage oriented reference frame is applied to Grid Side Converter (GSC) to improve the dynamic performance of DFIG. The proposed scheme enhances the Low Voltage ride through capability of Wind farm by providing reactive Power support under adverse grid conditions. The Proposed scheme also counteracts the ripples in DC Link voltage, stator/rotor currents and stator/reactive power to fulfill the grid code commitments in weak grid.Simulation results are presented to verify the feasibility and robustness of the proposed control scheme.